PERAN ORDER INVESTOR DALAM MENJELASKAN TERBENTUKNYA POLA VOLUME PERDAGANGAN DI BURSA EFEK INDONESIA - Syamni, Ghazali (UI Scholars Hub, 2011)
The purpose of this study is to analyze the role of informed and uninformed investor in explaining the formation of the pattern of trading volume in the Indonesian Stock Exchange (IDX). The data which is used in this study is the data of the transaction history-corporate edition demand and order history stock on the company which included LQ-45 in the period of March, April and May 2005 from the IDX. The data analysis method used multiple regression analysis with regress all order status to trading volume. The results of this study show that informed investor order is related significantly with trading volume on each interval. Otherwise the placement of uninformed investor order either uninformed buy or uninformed sale is mostly not related significantly on trading volume. That finding gives the indication that only informed investor order is more plays in explaining trading volume pattern. Whereas, if it is seen by order status, this study finds that mostly order status amend, open and withdraw are not influenced significantly to trading volume. This means that trading volume is commonly driven by order match status, specifically informed buy match and informed sale match.